Recommendations for nutritional supplements for dry eye disease: current advances - Cong, Ying; Zhang, Yibing; Han, Yutong; Wu, Yunlong; Wang, Dan; Zhang, Bingjie (Frontiers in Pharmacology, 2024)
Dry eye disease (DED) represents a prevalent ocular surface disease. The development of effective nutritional management strategies for DED is crucial due to its association with various factors such as inflammation, oxidative stress, deficiencies in polyunsaturated fatty acids (PUFAs), imbalanced PUFA ratios, and vitamin insufficiencies. Extensive research has explored the impact of oral nutritional supplements, varying in composition and dosage, on the symptoms of DED. The main components of these supplements include fish oils (Omega-3 fatty acids), vitamins, trace elements, and phytochemical extracts. Beyond these well-known nutrients, it is necessary to explore whether novel nutrients might contribute to more effective DED management. This review provides a comprehensive update on the therapeutic potential of nutrients and presents new perspectives for combination supplements in DED treatment.